GAMBARAN PELAKSANAAN SURVEILANS EPIDEMIOLOGI TUBERKULOSIS (TBC) DI RSUD SYEKH YUSUF GOWA - Helma Liana Safitri. M helma; Numulia Wunaini Ngkolu; Ardianti; Iismayanti; Mohammad Ardani Samad; Nur Alfia Usman (LPPM Universitas Awal Bros, 2026)
Background, The role of epidemiological surveillance in hospitals is one of the efforts to overcome the problem of infectious and non-infectious diseases, reduce morbidity, prevent death, cure patients and prevent the occurrence. The purpose of the study was to determine the description of the implementation of Tuberculosis Epidemiology Surveillance (TBC) at Syekh Yusuf Gowa Hospital. This method uses qualitative research. Data collection conducted interviews with the Surveillance Coordinator, Surveillance officers, Nurses, Medical records officers. Results and Conclusions Based on the input of the series of implementation of Tuberculosis Epidemiology Surveillance (TBC) at Syekh Yusuf Hospital, it was carried out by nurses in the Dots polyclinic and for other units only supporting the availability of TBC data, namely the Medical Records Installation, Laboratory, Epidemiological Surveillance and surveillance guidelines do not yet exist. Based on the Surveillance Process Series from data collection to data analysis and interpretation carried out by Nurses in the DOTS polyclinic, Based on the Surveillance Output, the achievement of surveillance indicators has been achieved and is in accordance with the specified target. Suggestions, Improve human resources so that the Hospital assigns employees in accordance with the established Education classification standards.